ANALISIS MINAT MENABUNG PADA BANK SYARIAH DI KALANGAN SISWA SMA DI KOTA MEDAN (STUDI KASUS: SISWA MADRASAH ALIYAH NEGERI) - Muhammad Abdallah; Irsyad Lubis (Departemen Ekonomi Pembangunan USU, 2015)
This study aims to determine Madrasah Aliyah Negeri students in Medan interest of saving Islamic bank in Medan. This research is descriptive quantitative research using primary data. The variables used in this research consisted of a bank's reputation, confidence, and location as the independent variable and the interest of saving the student as the dependent variable. Sampling technique is done by simple random sampling using 100 students of Madrasah Aliyah Negeri in Medan as a sample. The Methods of data collection use a self administrated survey, by giving questionnaires. The method used in this research is the descriptive analysis. Based on the results of analysis, it was found that Madrasah Aliyah Negeri students' interest in saving in Islamic banks in Medan is still low. Based on the data obtained it is known that bank reputation variables, beliefs, and location affect student interest in the Madrasah Aliyah Negeri decided to save the Islamic bank in Medan. The main obstacle that affects Madrasah Aliyah Negeri students' interest to save their money in Islamic banks is the location away from home.Keywords: Savings interest, Islamic banks, Madrasah Aliyah Negeri students in Medan.